2004
DOI: 10.1124/mol.65.5.1269
|View full text |Cite
|
Sign up to set email alerts
|

Cav1.3 Is Preferentially Coupled to Glucose-Induced [Ca2+]i Oscillations in the Pancreatic β Cell Line INS-1

Abstract: The link between Ca 2ϩ influx through the L-type calcium channels Ca v

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
4
15
0
Order By: Relevance
“…Because INS-1 cells express two distinct L-VGCC subtypes, Ca v 1.2 and Ca v 1.3, we sought to elucidate the role of Ca v 1.2 and Ca v 1.3 in mediating GLP-1-potentiated GSIS in these cells by use of dihydropyridine-resistant mutants of these two channels. We have previously used this approach to demonstrate a preferential role for Ca v 1.3 in mediating GSIS (Liu et al, 2003) and glucose-stimulated [Ca 2ϩ ] i oscillations (Liu et al, 2004). In the present study, we find that both Ca v 1.2 and Ca v 1.3 can couple to GLP-1 potentiation of GSIS, but to different degrees.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Because INS-1 cells express two distinct L-VGCC subtypes, Ca v 1.2 and Ca v 1.3, we sought to elucidate the role of Ca v 1.2 and Ca v 1.3 in mediating GLP-1-potentiated GSIS in these cells by use of dihydropyridine-resistant mutants of these two channels. We have previously used this approach to demonstrate a preferential role for Ca v 1.3 in mediating GSIS (Liu et al, 2003) and glucose-stimulated [Ca 2ϩ ] i oscillations (Liu et al, 2004). In the present study, we find that both Ca v 1.2 and Ca v 1.3 can couple to GLP-1 potentiation of GSIS, but to different degrees.…”
Section: Discussionsupporting
confidence: 45%
“…Thus, endogenous L-type channels can be blocked with a dihydropyridine drug such as nifedipine, and characteristics of the expressed mutant channels can be examined in isolation. Using this system, we previously reported that Ca v 1.3 is preferentially coupled to glucosestimulated insulin secretion (Liu et al, 2003) and [Ca 2ϩ ] in oscillations (Liu et al, 2004) in INS-1 cells, and that Ca v 1.2 and Ca v 1.3 are differentially coupled to potentiation of GSIS by an effector protein activated by cyclic AMP 2 (EPAC2)-selective analog of cAMP (Liu et al, 2006). Here, we report that Ca v 1.3 is preferentially coupled to GLP-1 potentiation of GSIS, but that Ca v 1.2 and Ca v 1.3 are not different in their ability to mediate GIP potentiation of GSIS.…”
mentioning
confidence: 99%
“…Liu et al have previously performed studies on the role of Ca V 1.2 versus Ca V 1.3 in INS-1 cells. They found that Ca V 1.3 was responsible for insulin secretion and calcium influx into the cells (Liu et al 2003(Liu et al , 2004. In these studies, the pore-forming units of the channels were over-expressed on top of normal expression patterns without taking into account constitutive expression of Ca V 1.2 and Ca V 1.3.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 60-70% of the rat whole-cell Ca 2C current in b-cells is sensitive to dihydropyridines (Schulla et al 2003, Huang et al 2004, Taylor et al 2005. The major dihydropyridine-sensitive calcium channels in rat b-cells are Ca V 1.2 or Ca V 1.3, with different studies emphasising the role of either one (Iwashima et al 1993, Liu et al 2004, Taylor et al 2005. Ca 2C currents that can be inhibited by u-conotoxin GVIA, which is known to block Ca V 2.2, have been reported in rat b-cells, but their role in insulin secretion is controversial (Satin et al 1995, Sher et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown previously that the neuroendocrine-specific channel Ca v 1.3 is preferentially coupled to GSIS (Liu et al, 2003) and glucose-stimulated Ca 2ϩ oscillations (Liu et al, 2004) in the rat insulinoma cell line INS-1. In contrast, we reported previously that both Ca v 1.2 and Ca v 1.3 can mediate GSIS potentiated by 8-Br-cAMP, but that only Ca v 1.2 can mediate potentiation of GSIS by activation of exchange protein activated by cAMP2 (EPAC2) independently of protein kinase A activation (Liu et al, 2006).…”
mentioning
confidence: 99%